PEMANFAATAN INSTAGRAM SEBAGAI STRATEGI KOMUNIKASI PENYIAR RADIO MADAMA FM (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
The main problem of this research is how to use Instagram as a communication strategy for Radio Madama broadcasters, presenting two substantive issues: 1) What is the strategy Madama Radio broadcaster's communication in using Instagram? 2) Anything Madama Radio announcer's challenges in using Instagram? This research aims to find out the communication strategy of Radio Madama broadcasters in Using Instagram and knowing what it is is a challenge Madama Radio broadcaster in using Instagram. This type of research is qualitative research using a mass communication approach. The data sources for this research are the broadcaster and social media manager for Radio Madama. Next, the method of Data collection used is observation, interviews, documentation, and reference tracking. Then, data processing and analysis techniques are carried out with three stages, namely: data reduction, data presentation, and withdrawal conclusion. The results of this research show that 1) Broadcaster communication strategy. Radio Madama's using Instagram includes: utilizing Instagram features, using hashtags, highlighting the latest trends, giving away, uploading consistent content, collaborating and partnerships, and doing promotion 2) Challenges for Radio Madama broadcasters in utilization of Instagram create engaging and relevant content, addressing the mood and adapting the broadcaster's style and ability to adapt to the space digital. The implication of this research is: to continue to strive to create creative and quality visuals that not only entertain but also educate the public, especially young people, and carry out evaluations of performance and create a clear content structure and plan in content creation so that improvements can be made in the future.